Attachment Styles, Gratitude, Forgiveness & Dyadic Adjustment as predictors of Marital Satisfaction - Mrs. Harleen Sidhu (International Journal of Indian Psychȯlogy, 2025)
Marriage is virtually found in all societies, and a majority of individuals in every society get married at least once in their lifespan. It has been established that the satisfaction of married couples is even more important than the marriage itself. Taking an inspiration from John and Julie Gottman’s Sound House Relationship Theory, the present study has attempted to study the effect of attachment style, gratitude, expression of gratitude, forgiveness, and dyadic adjustment on marital satisfaction. The study comprised of 200 married males and females (100 males & 100 females) between the age group of 25-50 years. Anxious & Avoidant Attachment styles are found to be negatively correlated with marital satisfaction whereas, gratitude, expression of gratitude, forgiveness & dyadic adjustment are positively correlated with marital satisfaction. Apart from this, a significant difference in gender in marital satisfaction is found. Females are found to have a lowered marital satisfaction as compared to males. Lastly, the duration of marriage is also seen to impact marital satisfaction. Individuals in 5 years and below of marriage reported to have higher marital satisfaction than those married for 10 years and above.